Lysine-Enriched Cecropin-Mellitin Antimicrobial Peptides with Enhanced Selectivity - Sato, Hiromi (American Society for Microbiology (ASM), 2008)
Lysine-enriched analogs of the cecropin-mellitin hybrid peptide, CA(1-7) M(2-9) (designated CM15), designed with optimized amphipathicity, retained antimicrobial activities similar to that of wild-type CM15 and had substantially reduced levels of hemolytic activity and cytotoxicity toward cultured macrophages, resulting in enhanced selectivity. These lysine-enriched analogs provide templates for improved CM15 peptide or peptidomimetic antibiotics.